2017
DOI: 10.1186/s13075-017-1280-6
|View full text |Cite
|
Sign up to set email alerts
|

Direct-acting antiviral agents in the therapy of hepatitis C virus-related mixed cryoglobulinaemia: a single-centre experience

Abstract: BackgroundThe efficacy and safety of direct-acting antiviral agents (DAAs) were evaluated in a cohort of prospectively enrolled patients with hepatitis C virus (HCV)-related mixed cryoglobulinaemia (MC), an immune complex-mediated vasculitis of small and medium vessels in which the pathogenetic role of HCV has been clearly established.MethodsTwenty-two patients received DAAs. Clinical and laboratory features were recorded at baseline, every 4 weeks until the end of treatment (EoT), and 12 weeks afterwards. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 36 publications
8
38
1
Order By: Relevance
“…Thus, the presence of cryoglobulinaemia was a prognostic factor of non‐response independent from the severity of liver disease, or other well‐known prognostic factors . In this study, both intention to treat and per protocol analyses confirmed the excellent virological outcome reported by previous studies on CV or MC patients treated with DAAs, hindering a valuable logistic regression analysis to identify outcome predictors. In other words, using DAAs, it was not possible to find significant differences in SVR rates between cryoglobulinaemic patients and controls.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Thus, the presence of cryoglobulinaemia was a prognostic factor of non‐response independent from the severity of liver disease, or other well‐known prognostic factors . In this study, both intention to treat and per protocol analyses confirmed the excellent virological outcome reported by previous studies on CV or MC patients treated with DAAs, hindering a valuable logistic regression analysis to identify outcome predictors. In other words, using DAAs, it was not possible to find significant differences in SVR rates between cryoglobulinaemic patients and controls.…”
Section: Discussionsupporting
confidence: 54%
“…Data regarding these new IFN‐free regimens for the treatment of CV patients are still limited, and based on uncontrolled studies and short follow‐ups. These studies are generally consistent with high rates of symptom remission in patients with sustained virological response (SVR), as well as a high tolerance of therapy …”
Section: Introductionsupporting
confidence: 55%
“…Namely, approximately half of CHC‐associated cryoglobulin disappeared after SVR. Thus, for patients with spontaneous HCV clearance, the MC prevalence of 34.6% is close to the proposed range based on the CHC studies (half of 40%‐60%), but is much higher than that of essential MC (0.001%) . The persistence of MC after viral clearance suggests that HCV antigens are not an unfailing component of cryoprecipitating immune complexes .…”
Section: Discussionsupporting
confidence: 69%
“…As mentioned, 40%‐60% of CHC patients exhibit circulating cryoglobulins . The clearance rate of cryoglobulin ranged from 35% to 59% in CHC patients who achieved an SVR by using DAAs and ranged from 43.6% to 57% in those who achieved an SVR by using interferon‐based therapy. Namely, approximately half of CHC‐associated cryoglobulin disappeared after SVR.…”
Section: Discussionmentioning
confidence: 94%
“…Eradicating hepatitis C infection results in numerous health benefits, including reduced rates of allcause mortality, cirrhosis, hepatic decompensation, and HCC. (33,37,(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109)(110) Successful treatment also confers improvement in extrahepatic manifestations of HCV disease, including cryoglobulinemic vasculitis (111)(112)(113)(114)(115)(116) and HCV-related non-Hodgkin lymphoma and other lymphoproliferative disorders, (117)(118)(119)(120)(121)(122)(123)(124)(125) as well as improved productivity and quality of life. (34,35,(126)(127)(128)(129)(130)(131) Given these and other benefits associated with virologic cure, the HCV guidance panel strongly recommends antiviral treatment for all adults with acute or chronic HCV infection (except those with a short life expectancy that cannot be remediated).…”
Section: Fib-4 Scorementioning
confidence: 99%